2001
DOI: 10.1164/ajrccm.163.3.9912052
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide in Vascular Permeability after Combined Burns and Smoke Inhalation Injury

Abstract: Patients with severe burn and/or smoke inhalation injury suffer both systemic and pulmonary vascular hyperpermeability. We hypothesized that nitric oxide (NO) produced by inducible nitric oxide synthase (iNOS) plays a role in the changes in microvascular permeability seen with this injury. To test the hypothesis, we administered mercaptoethylguanidine (MEG), a selective iNOS inhibitor, to conscious sheep subjected to a combined smoke inhalation and third-degree burn injury to 40% of total body surface area. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
100
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 26 publications
7
100
0
2
Order By: Relevance
“…22 Whereas constitutively expressed endothelial NOSproduced NO is considered to have protective effects on the vessel wall, iNOS may have an important role in mediating oxidative stress. 23 In addition, iNOS is also involved in the process of healing after injury. 24 Mechanical injury to the vessel wall is associated with increased iNOS expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Whereas constitutively expressed endothelial NOSproduced NO is considered to have protective effects on the vessel wall, iNOS may have an important role in mediating oxidative stress. 23 In addition, iNOS is also involved in the process of healing after injury. 24 Mechanical injury to the vessel wall is associated with increased iNOS expression.…”
Section: Discussionmentioning
confidence: 99%
“…The rodent model has been reported to produce notoriously high levels of NO compared with larger animals. 23 It is currently unclear how uncoupling may occur in CS-exposed mice. However, it is notable that L-arginine treatment prevented endothelial dysfunction in rabbits exposed to tobacco smoke and normalized coronary vasomotion in long-term smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Kristof and colleagues showed that NOS2 knockout mice were more resistant to LPS-induced lung injury than were wild-type mice (23). Moreover, treatment with NOS2 inhibitors seems to prevent ALI in sheep after burn and smoke inhalation injury (35,36). On the other hand, there are reports suggesting a beneficial role of ·NO in ALI based on the following: (1 ) it downregulates the expression of adhesion molecules, resulting in a reduction in the migration and accumulation of neutrophils (37); (2 ) it inhibits cytokine production (38); and (3 ) in a clinical trial, as had been previously shown for some animal models (39), the use of NOS inhibitors in patients with sepsis resulted in an increase in mortality (40).…”
Section: Discussionmentioning
confidence: 99%
“…Both N -nitro-L-arginine methyl ester (L-NAME), a nonselective NOS inhibitor, and aminoguanidine, a partially selective iNOS inhibitor, suppress increased vascular permeability of second-degree burned skin in mice (27). The partially selective iNOS inhibitor mercaptoethylguanidine (MEG) decreases pulmonary microvascular permeability changes in sheep after combined burn and smoke inhalation injury (26). N G -(1-iminoethyl)-L-lysine, a selective iNOS inhibitor, improves renal function in rats subjected to renal artery cross-clamping (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications report beneficial ef-fects of highly selective iNOS inhibitors on myocyte damage in acute cardiac allograft rejection (30), ischemia-reperfusion injury in skeletal muscle (35), and multiple organ dysfunction in hemorrhagic shock (17). Numerous studies with partially selective iNOS inhibitors support a role for iNOS and NO in thermal injury (26), but definitive data with highly selective iNOS inhibitors are lacking.…”
mentioning
confidence: 99%